The Role of Environmental Sanitation and Personal Hygiene in Soil Transmitted Helminths Infection in School-Age Children in Banjarharjo Sub-district - EKANIASARI, MEVIANA DEA; WARDANI, DITA PRATIWI KUSUMA; MUJAHID, IKHSAN; ALMANFALUTHI, MUHAMMAD LUTHFI (Universitas Nahdlatul Ulama Surabaya, 2024)
Helminthiasis in school-age children can impede both physical and cognitive development. Poor personal hygiene practices are associated with various health issues among schoolchildren, including diarrhoea and helminth infections. A healthy environment is crucial for physical and mental well-being, whereas poor sanitation significantly increases the risk of infectious diseases. This study aims to examine the relationship between environmental sanitation, personal hygiene, and soil-transmitted helminth infections among school-age children in the Banjarharjo Sub-district. This analytic observational study employed a cross-sectional design and was conducted in July 2023. Data collection involved administering a personal hygiene and environmental sanitation questionnaire, alongside identifying soil-transmitted helminth (STH) eggs in faeces and nail samples using the MgSO4 sedimentation method. Participants were selected through purposive sampling based on predefined inclusion and exclusion criteria. The study population comprised school-age children from Banjarharjo District, with a final sample size of 58 children from Sindangheula Village and Cikuya Village. Data analysis was performed using the Fisher exact test. The results showed no association between environmental sanitation (faeces p = 0.583; nails p = 1.00) and personal hygiene (faeces p = 1.00; nails p = 1.00) and soil-transmitted helminth infection in both faeces and nail samples (p > 0.05). Therefore, the study found no significant relationship between environmental sanitation, personal hygiene, and soil-transmitted helminth infection among school-age children in Banjarharjo Sub-district. Keywords: Environmental sanitation, personal hygiene, school age, soil-transmitted helminths